Unravelling the effects of contemporary and historical range expansion on the distribution of genetic diversity in the damselfly Coenagrion scitulum. (3rd March 2014) - Swaegers, J.; Mergeay, J.; Therry, L.; Bonte, D.; Larmuseau, M. H. D.; Stoks, R.
Abstract Although genetic diversity provides the basic substrate for evolution, there are a limited number of studies that assess the impact of recent climate change on intraspecific genetic variation. This study aims to unravel the degree to which historical and contemporary factors shape genetic diversity and structure across a large part of the range of the range‐expanding damselfly Coenagrion scitulum (Rambur, 1842). A total of 525 individuals from 31 populations were genotyped at nine microsatellites, and a subset was sequenced at two mitochondrial genes. We inferred the importance of geography, environmental factors, and recent range expansion on genetic diversity and structure. Genetic diversity decreased going westwards, suggesting a signature of historical post‐glacial expansion from east to west and the presence of eastern refugia. Although genetic differentiation decreased going northwards, it increased in the northern edge populations, suggesting a role of contemporary range expansion on the genetic make‐up of populations. The phylogeographical context was proven to be essential in understanding and identifying the genetic signatures of local contemporary processes. Within this framework, our results highlight that recent range expansion of a good disperser can decrease genetic diversity and increase genetic differentiation which should be considered when devising suitable conservation strategies.